2001
DOI: 10.1017/s0031182001007594
|View full text |Cite
|
Sign up to set email alerts
|

The Egyptian mongoose,Herpestes ichneumon, is a possible reservoir host of visceral leishmaniasis in eastern Sudan

Abstract: Investigations were made on possible reservoir hosts of Leishmania donovani in 2 zoonotic foci of visceral leishmaniasis (VL) in Dinder National Park (DNP) and the peri-domestic habitats of adjacent villages of eastern Sudan. Animals were captured, in November 1997-1998 and April-May 1999 and examined for L. donovani infection using light microscopy and 2 sensitive Polymerase Chain Reaction (PCR) systems. Microscopy and PCR investigations were also used to determine the infection rates of L. donovani in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 21 publications
2
62
0
Order By: Relevance
“…20 A high infection rate of P. orientalis with L. donovani has been reported from uninhabited areas of Dinder National Park. 20 Subsequent studies identified infected mongoose 21 and humans in neighboring villages. 20 Moreover, a recent study done in Dinder National Park encountered Phlebotomus rodhaini infected with L. donovani.…”
Section: Discussionmentioning
confidence: 99%
“…20 A high infection rate of P. orientalis with L. donovani has been reported from uninhabited areas of Dinder National Park. 20 Subsequent studies identified infected mongoose 21 and humans in neighboring villages. 20 Moreover, a recent study done in Dinder National Park encountered Phlebotomus rodhaini infected with L. donovani.…”
Section: Discussionmentioning
confidence: 99%
“…But in all these cases, there was no parasite identification. Elnaim et al [18] described 2/14 Egyptian mongooses (Herpestes ichneumon), 1/168 A. niloticus and 1/8 Mastomys natalensis positive by smear detection and PCR. The first mention of specifically identified L. donovani in dogs was made by Mutinga et al [19], who isolated two stocks from Kenyan dogs, one of them (MCAN/KE/00/D2) related to L. donovani MON-36 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Sudanese VL is caused by various zymodemes of the Leishmania donovani complex (Ashford et al, 1992;Oskam et al, 1998). The main vector appears to be Phlebotomus orientalis (Ashford et al, 1992) but naturally infected P. rodhaini have been collected in the east of the country (Elnaiem et al, 2001). In a recent study based in the village of Surogia, in Khartoum state, both P. orientalis and P. rodhaini have been detected in northern Sudan for the first time.…”
mentioning
confidence: 99%
“…Forty-two (3.1%) of the specimens were identified as P. orientalis and eight (0.6%) as P. rodhaini. Although P. orientalis is the main vector of the parasites causing VL in Sudan (Ashford et al, 1992;Elnaiem et al, 2001;Hassan et al, 2004), neither it nor P. rodhaini have previously been recorded in northern Sudan. It is possible that (1) the distribution of these two species in northern Sudan is restricted to certain habitats that have not previously been explored by entomologists; and/or (2) these two species have not previously been detected in northern Sudan because they only occur there in very low numbers.…”
mentioning
confidence: 99%